IMC Strategies of K-EXPO 2024: Localizing Korean Agro & Fisheries - Dhyana, Dharma, DD; Dewi, Helga Liliani Cakra, HLCD; Nurhayati, Kristina (JURNAL KOMUNIKASI INDONESIA, 2026)
The global rise of the Korean Wave (Hallyu) has created a significant market for Korean products in Indonesia, one of its key export destination. While Korean food (K-Food) is popular, Korean seafood (K-Seafood) remains relatively unknown, presenting a unique marketing challenge. This study examines the Integrated Marketing Communication (IMC) strategies implemented by K-EXPO 2024 to localize and promote K-Seafood to Indonesian consumers, addressing key challenges such as low product awareness and the prevalent stereotype of K-Food being non-halal. Employing a qualitative approach, this research draws on in-depth interviews with key practitioners, including the K-EXPO 2024 Project Head and Promotion Manager, an agro-trade representative, and Indonesia's Minister of Trade. Thematic analysis reveals that the event's success stemmed from a sophisticated IMC strategy. This finding aligned with the Indonesian government's perspective that market penetration hinges on business-led promotional innovation rather than direct trade policy. The findings show that the strategy rested on three pillars: (1) strong message consistency centered on halal certification as a foundational "trust marker"; (2) a multichannel communication approach blending culturally resonant influencers, a transparent informational website, and high-visibility offline advertising; and (3) brand image reinforcement through strategic partnerships with cultural bodies like KOCCA and the use of storytelling linking the product to the aspirational values of the Korean Wave. This study concludes that K-EXPO 2024 offers a practical model for cross-cultural marketing, demonstrating that a multidimensional IMC approach rooted in deep cultural adaptation is critical for transcending cultural barriers and achieving sustainable market growth.